Evaluating K13 and Merdeka Curriculum Implementation in Primary Education: A Comprehensive Literature Review - Pratiwi, Agustin Adelia Sisca; Elizar; Apriza, Berta; Sumarno (Indonesian Journal of Educational Research and Review, 2024)
Elementary education in Indonesia has undergone significant reforms with the introduction of the K13 Curriculum and the Merdeka Curriculum. These changes aim to enhance the quality of education and equip students with 21st-century skills. This study seeks to analyze the differences in the implementation of the Merdeka Curriculum and the K13 Curriculum through a systematic literature review. The research employed the SLR (Systematic Literature Review) method using Google Scholar as the primary database. The literature reviewed was limited to the period from 2019 to 2023, using a three-stage keyword search process. The first stage resulted in 3,340 documents with the keyword "K13 Curriculum." The second stage yielded 492 documents with the keywords "Merdeka Curriculum" and the addition of "AND" between these terms. In the third stage, adding the keyword "in elementary school" and the term "AND" between the earlier keywords narrowed the results to 225 documents. These documents were further filtered based on inclusion criteria, resulting in 7 articles for detailed analysis. The analysis revealed significant differences in focus and approach between the two curricula. The K13 Curriculum emphasizes the development of affective, cognitive, and psychomotor competencies through a scientific approach, while the Merdeka Curriculum prioritizes the Pancasila Student Profile through P5 (Project-Based Learning) and differentiated instruction. These changes pose challenges for educators, particularly regarding understanding and skill acquisition in implementing the curriculum.